1972
DOI: 10.1017/s0031182000044991
|View full text |Cite
|
Sign up to set email alerts
|

Life cycle of a new echinostome from Egypt, Echinostoma liei sp.nov. (Trematoda: Echinostomatidae)

Abstract: A 37-spined Egyptian echinostome, Echinostoma liei sp.nov., is described in adult and larval stages. The parasite develops readily in the laboratory in chicks and ducklings, hamsters and rats. Its natural final host in or near irrigation ditches of the Nile delta involves the roof rat, Egyptian giant shrew and aquatic bird hosts. Developmental forms are described from infection of the NIH strain of Biomphalaria glabrata in the laboratory. B. alexandrina, is infected in the normal habitat in Egypt and contains … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0
1

Year Published

1981
1981
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(24 citation statements)
references
References 19 publications
1
22
0
1
Order By: Relevance
“…Biomphalaria glabrata is a hermaphroditic snail able to self-fertilize. The strain of E. caproni (Jeyarasasingam et al, 1972) has been maintained for several years in our laboratory. Echinostoma caproni is a hermaphroditic parasite with an indirect life cycle involving three hosts.…”
Section: Studied Individualsmentioning
confidence: 99%
“…Biomphalaria glabrata is a hermaphroditic snail able to self-fertilize. The strain of E. caproni (Jeyarasasingam et al, 1972) has been maintained for several years in our laboratory. Echinostoma caproni is a hermaphroditic parasite with an indirect life cycle involving three hosts.…”
Section: Studied Individualsmentioning
confidence: 99%
“…Mice were infected with 6 cysticercoids/mouse, and drug treatments were commenced at about 3 weeks postinfection (p.i.). Echinostoma caproni, an isolate from Egypt that was obtained from the Danish Bilharziasis Laboratory (Charlottenlund, Denmark), was reared in BALB/c mice and Biomphalaria glabrata snails (Jeyarasasingam et al 1972;Christensen et al 1988;Fried and Human 1996). Mice were infected with 25 metacercariae, and drug treatments were commenced at days 18±24 p.i.…”
Section: Parasitesmentioning
confidence: 99%
“…, when discussing 37-collar-spined echinostomes, suggested that Echinostoma caproni Richard, 1964 is the correct name for an Egyptian species described by Jeyarasasingam et al (1972) as E. liei and Echinostoma trivolvis (Cort, 1914) Kanev, 1985 the correct name for a North American form described by Beaver (1937) from north central USA as E. revolutum. Our study uses the Egyptian and North American species and refers to them as E. caproni and E. trivolvis, respectively.…”
Section: Introductionmentioning
confidence: 99%